2003
DOI: 10.1023/b:plan.0000009259.75314.15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two phosphate transporters from barley; evidence for diverse function and kinetic properties among members of the Pht1 family

Abstract: Putative phosphate transporters have been identified in a barley (Hordeum vulgare L.) genomic library by their homology to known phosphate transporters from dicot species. The genes designated HORvu;Pht1;1 and HORvu;Pht1;6 encode proteins of 521 and 535 amino acids respectively with 12 predicted membrane-spanning domains and other motifs common to the Phtl family of phosphate transporters. HORvu;Pht1;1 is expressed exclusively in roots and is strongly induced by phosphate deprivation. HORvu;Pht1;6 is expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
177
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(190 citation statements)
references
References 19 publications
10
177
0
3
Order By: Relevance
“…For instance, the Ph1; 6 gene, which encodes a transporter of low affinity of phosphorus and is highly expressed in shoots (Rae et al, 2003), may be a possible candidate gene involved in the cell exclusion of glyphosate. Likewise, the Ph2; 1 gene, that is encoded in the plastids (Rausch et al, 2004) may be involved in the chloroplast exclusion of glyphosate.…”
Section: Reduction Of Absorption or Translocationmentioning
confidence: 99%
“…For instance, the Ph1; 6 gene, which encodes a transporter of low affinity of phosphorus and is highly expressed in shoots (Rae et al, 2003), may be a possible candidate gene involved in the cell exclusion of glyphosate. Likewise, the Ph2; 1 gene, that is encoded in the plastids (Rausch et al, 2004) may be involved in the chloroplast exclusion of glyphosate.…”
Section: Reduction Of Absorption or Translocationmentioning
confidence: 99%
“…Furthermore, attempts to improve tolerance to P deficiency through transgenic approaches have so far not yielded great success. Overexpression of the rootspecific high-affinity transporter gene HORvuPht1;1 from barley did not enhance P uptake of transgenic plants grown in soil or in hydroponics although the authors had shown in an initial experiment that HORvuPht1;1 overexpression increased P uptake in cultured rice cells (Rae et al 2003(Rae et al , 2004. A phytase gene from Aspergillus niger in transgenic Trifolium subterraneum improved P uptake of plants supplied with phytate and grown in agar under sterile conditions (Richardson et al 2001), but this positive effect was not always seen in soil-grown plants (George et al 2005), possibly because phytate was bound to soil particles and therefore not available as a substrate for phytase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was confirmed that HvPHT1;1 is a high-affinity Pi transporter with a K m of 1.9 mM when expressed in Xenopus laevis oocytes (Preuss et al, 2011), suggesting that HvPHT1;1 is involved in Pi acquisition. HvPHT1;6 is expressed in both shoots and roots (Huang et al, 2008) and localized in the leaf phloem tissue (Rae et al, 2003). It displays unsaturated uptake in a millimolar range of Pi concentrations when expressed in oocytes (Preuss et al, 2010), suggesting that HvPHT1;6 is involved in Pi retranslocation.…”
mentioning
confidence: 99%